Regions of time and internet: modelling: an application of the space-time trip (RASTT) model to the USA internet market - Robert Baker (European Regional Science Association (ERSA), 2002)
The mathematical analysis of the Internet and World Wide Web (WWW) is distinctly aspatial at present, with the transaction flows defined specifically by time-dependent indices (such as, the Internet Weather Report). How should the Internet and WWW be viewed as a geographical system where both space and time are fundamental to interaction? The retail aggregate space-time (RASTT) model has been developed previously to study trips to and from shopping malls and this model may provide some insights into the framing of this question. The RASTT model can be developed from a time-dependent random walk from an ensemble of home-based computers sending and receiving transactions through a network of sites. The spatial solution forms very weak gravity interactions and the time-dependent solutions are demand waves circumnavigating the Earth. Recent experimental results from Microsoft Research support these conclusions. These flows have the interesting property of moving either forwards or backwards through regions of time relative to the rotation of the Earth. The model can be developed to show bias in flows to USA sites and by using similarity arguments, the transaction demand wave across the USA can be derived by using a power law assumption of network connectivity.
Keywords: 330